Burial mounds in Europe and Japan : comparative and contextual perspectives - Knopf, Thomas; Steinhaus, Werner; Fukunaga, Shin'ya, 1959- (Comparative and global perspectives on Japanese archaeology., 2018)
This title brings together specialists of the European Bronze and Iron Age and the Japanese Yayoi and Kofun periods for the first time to discuss burial mounds in a comparative context. The text aims to strengthen knowledge of Japanese archaeology in Europe and vice versa.